The relational context of early development: consequences of maltreatment in infancy and effective early intervention - Stacks, Ann M. (The Oxford handbook of developmental psychology and the law, 2024)
During pregnancy and the first three years of life, the environment impacts gene expression and neurobiology, which has a cascading effect on health and development across the lifespan. Understanding these effects is critical to assessing and responding to the impact of maltreatment during this developmental window. The current chapter provides this background knowledge. First, the science of child development is presented together with child welfare laws that support the well-being of maltreated children. Next, the impact of maltreatment during the embryonic, fetal, and infant periods of human development is reviewed. Finally, promising relationship-based interventions for maltreating families are described.